Second Lead Syndrome in The Reception of Romantic Relationships by Indonesian Female K-Drama Audiences - Gissena, Annisa; Arymami, Dian; Agusta, Rivga (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
The Second Lead Syndrome, popular among Indonesian K-drama viewers, involves favoring the second lead over the main character in love triangles, sparking audience contestation. Start-Up (2020) is one of the K-dramas that sparked it and divided its audience into Nam Do-san Team and Han Ji-pyeong Team based on differences in audience views, so this descriptive qualitative research was conducted to describe Han Ji-pyeong Team's reception of romantic relationships in Start-Up. This research combines Hall's Reception Theory, the participatory audience concept, and Sternberg's Triangular Theory of Love. Research data was obtained through in-depth interviews with six informants representing Han Ji-pyeong Team.The findings indicate that the informants perceive the romantic relationships in dominant-hegemonic and negotiating positions. They support the second lead character, Ji-pyeong, by negotiating the romantic relationships shown. They acted on this reception by expressing emotions, preferences, and narrative interpretation on social media, driven by their preferences, identification, and parasocial relationships with the second lead. Their actions become a collective activity contributing to forming a popular culture, the second lead syndrome. This study explores audience reception of romantic relationships in K-dramas and their participation, setting an academic precedent for the second lead syndrome in Indonesian context.